1994
DOI: 10.1177/070674379403900110
|View full text |Cite
|
Sign up to set email alerts
|

Validation d'une échelle d'attitudes alimentaires auprès d'une population québécoise francophone

Abstract: The Eating Attitudes Test (EAT-26) is one of the most frequently used screening questionnaires for anorexia and bulimia nervosa for use with clinical and general populations. Although the psychometric qualities of the instrument have been reported for the English version, little has been done to date to validate a French version. A french version of the EAT-26 was distributed to anglophone students and francophone students, as well as anglophone and francophone patients. Overall, the results demonstrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 9 publications
0
38
0
Order By: Relevance
“…Their answers were then recoded into transformed scores following the recommendations of Garner et al [24]: the six-point scale was recoded into a four-point scale ranging from 0 to 3 in which 0 is assigned to the three responses that represent the least symptomatic answers and 3 represents the most symptomatic answer. The French version of the EAT-26 [30] was validated on an adolescent and adult sample of clinical and nonclinical females (n=1,196) and provided results that were similar to those obtained with the original version. Indeed, the study of Leichner et al [30] confirmed the original factor structure and found modest to acceptable internal consistency coefficients, ranging from α=0.54 (oral control) to 0.86 (global scale).…”
Section: Disturbed Eating Behaviorsmentioning
confidence: 65%
See 1 more Smart Citation
“…Their answers were then recoded into transformed scores following the recommendations of Garner et al [24]: the six-point scale was recoded into a four-point scale ranging from 0 to 3 in which 0 is assigned to the three responses that represent the least symptomatic answers and 3 represents the most symptomatic answer. The French version of the EAT-26 [30] was validated on an adolescent and adult sample of clinical and nonclinical females (n=1,196) and provided results that were similar to those obtained with the original version. Indeed, the study of Leichner et al [30] confirmed the original factor structure and found modest to acceptable internal consistency coefficients, ranging from α=0.54 (oral control) to 0.86 (global scale).…”
Section: Disturbed Eating Behaviorsmentioning
confidence: 65%
“…The French version of the EAT-26 [24,30] was used in the fourth study as a selfreport inventory to evaluate the presence of disturbed eating behaviors. This instrument comprises a global scale and three subscales: (1) dieting, (2) bulimia and food preoccupation, and (3) oral control.…”
Section: Disturbed Eating Behaviorsmentioning
confidence: 99%
“…Cronbachs alpha is .85, and a cutoff of 20 is felt to reliably identify maladaptive eating. Equivalence of the EAT-26 in English and (our own) French form is demonstrated according to factor structure, internal consistency, performance of cutoffs, and relationship to convergent measures (Leichner, Steiger, Puentes-Neuman, Perreault & Gottheil, 1994). High EAT-26 scores imply pathological response.…”
Section: The Eating Attitudes Test (Eat-26)mentioning
confidence: 92%
“…Plate cleaning tendency, consumption monitoring and mood were translated into French and assessed on agreement scales anchored (À3) strongly disagree and (+3) strongly agree. Dieting behavior was assessed with the French translation (Leichner, Steiger, Puentes-Neuman, Perreault, & Gottheil, 1994) of the Eating Attitude Test (EAT-26; Garner, Olmsted, Bohr, & Garfinkel, 1982). Binge eating was assessed by a question from the Eating Disorders Examination (Fairburn & Cooper, 1993): ''Have there been any times when you have eaten a large amount of food in a short amount of time and you had a sense of loss of control about your eating?''…”
Section: Methodsmentioning
confidence: 99%